2021
DOI: 10.1080/17400201.2021.1911792
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s experiences and meaning-making at a multicultural festival in Norway

Abstract: This article explores young people's experiences and meaning-making at a multicultural festival. Multicultural festivals aim to promote inclusion and challenge problem-oriented discourses in current debates on diversity and migration. Listening to youth voices from such a festival gives a sense of how young participants perceive representations of cultural difference, and how they relate these representations to their own identity and sense of belonging. The participants in our study are 86 young people from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…My Memory App was designed to allow the young festival participants to speak freely on site, that is, without adult supervision and presence, as they were experiencing the festival here-and-now. We first analyzed these interviews for an article (see Dewilde et al, 2021) about young people’s experiences and meaning-making. In this process, we experienced that some responses became more central to our analysis than others.…”
Section: Starting Point Positionality and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…My Memory App was designed to allow the young festival participants to speak freely on site, that is, without adult supervision and presence, as they were experiencing the festival here-and-now. We first analyzed these interviews for an article (see Dewilde et al, 2021) about young people’s experiences and meaning-making. In this process, we experienced that some responses became more central to our analysis than others.…”
Section: Starting Point Positionality and Methodsmentioning
confidence: 99%
“…As noted in the introduction, we first analyzed the data in line with the central concepts in our fields related to intercultural learning and citizenship (Dewilde et al, 2021). Returning to the data now anew, we made a conscious effort to listen openly to the recordings by prolonging the listening phase and delaying categorization.…”
Section: Starting Point Positionality and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation between variables will be determined by a series of statistical analyses. Prior research has indicated that attending to attendees' opinions, attitudes, and experiences of a festival can help identify how they perceive the festival as it relates to their own identity and sense of inclusion (Dewilde, et al, 2021). As a result of the aforementioned attributes of the True/False Film Fest, the research deemed attendees of this festival event to be the appropriate target population to explore personal experiences of diversity, equity, and inclusion within a festival setting.…”
Section: Methodsmentioning
confidence: 99%